Analisis Kompensasi Berbasis Kesejahteraan Holistik Terhadap Turnover Intention Karyawan - Budiyanto, Gatot; Halwatiah; Adianto; Hamdani, Rizki; Rusmana; Mulyadi, Edi (Jurnal Teknologi dan Bisnis Cerdas, 2025)
This PRISMA-guided systematic review synthesizes evidence on holistic welfare-based compensation and its association with turnover intention. Searches across Scopus, ScienceDirect, Taylor & Francis Online, Google Scholar, and SINTA targeted 2018–2025 peer-reviewed publications in Indonesian/English directly linking compensation components work flexibility, work–family support/FSSB, compensation & justice, mental-health support/EAP, recognition, and leadership/resources to intention to quit. Thirty-two studies met inclusion criteria (four meta-analyses, three systematic reviews, one randomized field experiment, and twenty-four quantitative studies). Thematic synthesis and SWiM vote counting indicated 28/32 studies reported reduced turnover intention when holistic components were implemented; 3/32 reported increases associated with psychological violence, absenteeism, and burnout/stress; 1/32 showed a nonsignificant direct effect but an indirect pathway via job satisfaction. Key mediators included job satisfaction, engagement, and motivation, while work–family conflict and burnout decreased. Findings align with the Job Demands–Resources framework: augmenting job resources enhances psychological functioning and dampens demands, thereby lowering intention to quit. We recommend a Holistic Total Rewards bundle combining structured flexibility, accessible work–family/FSSB practices, fair and transparent pay, EAP/mental-health supports, recognition, and supportive leadership; future research should use longitudinal/experimental designs, standardize indicators, and assess cost–benefit